MRI-Derived Scapular Superomedial Angle and Acromial Morphology: A Retrospective Cross-Sectional Reliability and Morphometric Association Study - Sami Kandefer; Volkan Gür; Mehmet Burak Gökgöz; Muhammet Ali Can; Metin Taş; Kemal Buğra Memiş; Mecit Kantarcı; Nizamettin Koçkara; Furkan Yapıcı (Journal of Clinical Medicine, 2026)
Background/Objectives: The magnetic resonance imaging (MRI)-derived scapular superomedial angle (SMA) may serve as a continuous descriptor of scapular geometry. We evaluated whether SMA is associated with acromial morphology, examined SMA and subacromial space (SAS) across acromial categories, and quantified measurement reliability. Methods: In this retrospective cross-sectional study, 306 shoulders from 279 patients (27 bilateral) were analyzed after screening 353 examinations. SMA and SAS were measured independently by two orthopedic observers, and acromial morphology was classified independently by two radiologists, all in blinded sessions. Reliability, group comparisons, receiver operating characteristic (ROC) analyses, and patient-level clustered generalized estimating equations were performed. Results: Interobserver reliability was excellent for SMA (intraclass correlation coefficient [ICC], 0.960) and SAS (ICC, 0.926), and intraobserver reliability was excellent for SMA and good for SAS (ICC, 0.944 and 0.848); acromial classification agreement was almost perfect (linear-weighted kappa, 0.980). SMA increased stepwise across Type I to III acromia (128.7°, 133.9°, 137.2°; p < 0.001), whereas SAS decreased (7.5, 6.8, 6.3 mm; p < 0.001). Each 1° SMA increase was independently associated with Type III morphology (adjusted odds ratio, 1.18; p < 0.001). SMA was not independently associated with rotator-cuff severity (p = 0.842). Because adjacent Type II–III differences approached the minimum detectable change, individual-level discrimination was limited. Conclusions: MRI-derived SMA is a reproducible descriptor associated with acromial morphology at the group level, but adjacent-category differences approached measurement error. SMA should not substitute for direct acromial classification, and external validation is required before clinical thresholds are considered.